(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
Abstract: The rapid development of Artificial Intelligence (AI) and digital technologies is profoundly transforming global economies, compelling countries to reconsider their reform strategies in order to enhance competitiveness, increase economic efficiency, and ensure sustainable development. For Azerbaijan, whose economy largely depends on energy resources, particularly hydrocarbon revenues, economic diversification has become even more crucial amid fluctuating energy prices, global geopolitical tensions, and climate change. AI technologies create significant opportunities for optimizing industrial processes, improving resource management, enhancing financial and fiscal services, and advancing education and human capital development. This article analyzes the advantages and potential risks of AI-based economic and social reforms within both international and local research contexts. AI technologies provide extensive opportunities to boost productivity in industry and agriculture, optimize energy and resource use, make financial services more inclusive, improve governance, and foster an innovative business environment. At the same time, automation and digital transformation may cause shifts in the labor market; therefore, reskilling, vocational training, and the development of human capital should be prioritized. The article offers recommendations for policymakers and regulators concerning infrastructure modernization, the strengthening of ethical and legal frameworks, ensuring social justice, and enhancing economic resilience. The conducted analysis shows that the effective implementation of AI can transform Azerbaijan’s oil-dependent economic model into a knowledge- and technology-driven, competitive, and sustainable economic system. At the same time, AI technologies create favorable conditions for regional cooperation, international investment, and the development of innovative startups. The article emphasizes the contribution of AI integration to the country’s economic diversification, social justice, and technological independence.